Professional Portfolio Management - Stewart, Scott (John Wiley & Sons, Incorporated, 2019)
A career's worth of portfolio management knowledge in one thorough, efficient guide Portfolio Management is an authoritative guide for those who wish to manage money professionally. This invaluable resource presents effective portfolio management practices supported by their underlying theory, providing the tools and instruction required to meet investor objectives and deliver superior performance. Highlighting a practitioner's view of portfolio management, this guide offers real-world perspective on investment processes, portfolio decision making, and the business of managing money for real clients. Real world examples and detailed test cases--supported by sophisticated Excel templates and true client situations--illustrate real investment scenarios and provide insight into the factors separating success from failure. The book is an ideal textbook for courses in advanced investments, portfolio management or applied capital markets finance. It is also a useful tool for practitioners who seek hands-on learning of advanced portfolio techniques. Managing other people's money is a challenging and ever-evolving business. Investment professionals must keep pace with the current market environment to effectively manage their client's assets while students require a foundation built on the most relevant, up-to-date information and techniques. This invaluable resource allows readers to: Learn and apply advanced multi-period portfolio methods to all major asset classes. Design, test, and implement investment processes. Win and keep client mandates. Grasp the theoretical foundations of major investment tools Teaching and learning aids include: Easy-to-use Excel templates with immediately accessible tools. Accessible PowerPoint slides, sample exam and quiz questions and sample syllabi Video lectures Proliferation of mathematics in economics, growing sophistication of investors, and rising competition in the industry requires advanced training of investment professionals. Portfolio Management provides expert guidance to this increasingly complex field, covering the important advancements in theory and intricacies of practice.